Battery packaging material applied to power battery packaging and preparation method thereof
By using components such as nanosilicon nitride and maleic anhydride in the power battery packaging materials, the compatibility of sodium alginate with nylon 6 and polystyrene alcohol is promoted, and the problem of poor material compatibility in the prior art is solved, the performance of the material is improved and the cost is reduced.
Patent Information
- Application Number
- CN202510058897.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Among the existing power battery packaging materials, polystyrene alcohol (PPO) and nylon 6 (PA6) have poor compatibility, resulting in poor processing and mechanical properties, and high production costs.
Using components such as nano-silicon nitride and maleic anhydride, sodium alginate is grafted on nano-silicon nitride through mono-esterification and di-esterification reactions, and hydrogen bonds are formed with nylon 6 and polysenol to reduce the melt viscosity ratio of PPO/PA6 and promote its compatibility.
It improves the processing performance and mechanical properties of battery packaging materials, reduces the production cost, and is more stable under high heat and high mechanical impact.
Smart Images

Figure BDA0005242261690000061 
Figure BDA0005242261690000071
Abstract
Description
Technical Field
[0001] The present invention relates to power battery technology, and in particular to a battery packaging material used for power battery packaging and a preparation method thereof. Background Art
[0002] In power battery packaging technology, polyphenylene ether (PPO) is usually used as a power battery packaging material. Since PPO is difficult to process and easily causes stress cracking, nylon 6 (PA6) can be used to improve its processing performance and stress cracking problem. However, PA6 is a highly crystalline material, while PPO is a non-crystalline material, and the compatibility between the two is very poor.
[0003] The paper "Study on the Performance of Aramid Fiber Reinforced Polyphenylene Oxide / Nylon 6 Alloy" (Wang Honghua, Mei Qilin, Xia Xue, et al. Study on the Performance of Aramid Fiber Reinforced Polyphenylene Oxide / Nylon 6 Alloy [J]. FRP / Composites, 2017, 000(006): 75-79.) discloses an aramid fiber reinforced polyphenylene ether / nylon 6 alloy and a preparation method thereof. The preparation method uses maleic anhydride grafted styrene-butadiene block copolymer (SEBS-MAH) to increase the capacity and toughen the polyphenylene ether / nylon 6 (PPO / PA6) alloy to prepare an aramid fiber (AF) reinforced PPO / PA6 / SEBS-MAH composite material. However, aramid fiber is easy to age and degrade, and is expensive and has a low cost-effectiveness. Therefore, the obtained battery packaging material has poor performance and high preparation cost. Summary of the invention
[0004] In order to solve the problems existing in the above-mentioned prior art, a first object of the present invention is to provide a battery packaging material used for power battery packaging, which has excellent performance and low preparation cost.
[0005] In order to solve the problems existing in the above-mentioned prior art, the second object of the present invention is to provide a method for preparing a battery packaging material used for power battery packaging, which has low cost and the prepared battery packaging material has excellent performance.
[0006] In order to solve the problems existing in the above-mentioned prior art, the third object of the present invention is to provide a power battery.
[0007] In order to achieve the first object of the present invention, the following technical scheme is adopted:
[0008] The invention provides a battery packaging material used for power battery packaging, which comprises the following components: 4-5 parts of sodium alginate, 8-10 parts of nano silicon nitride, 4-5 parts of maleic anhydride, 100-120 parts of polyphenylene ether, and 10-12 parts of nylon 6.
[0009] In specific implementation, by introducing nano silicon nitride with high thermal stability and good mechanical properties, damage to battery packaging materials can be avoided or reduced under high thermal shock and high mechanical shock, and maleic anhydride is creatively grafted onto the -OH group of nano silicon nitride to cause a monoesterification reaction, and then the -OH group on sodium alginate is reacted with the -COOH group on maleic anhydride monoester through a double esterification reaction, so that sodium alginate is grafted onto the nano silicon nitride. Sodium alginate can generate hydrogen bonds with nylon 6, and generate hydrogen bonds with the -OH end group and -O- segment of polyphenylene ether, and react with the -OH end group of polyphenylene ether. Nano silicon nitride, as an inorganic rigid particle and chemical cross-linking point, can reduce the melt viscosity ratio of PPO / PA6 and promote the compatibility of PPO and PA6, thereby further improving the processing performance, mechanical properties, etc. of PPO.
[0010] Preferably, the melting point of sodium alginate is below 100°C.
[0011] In specific implementation, sodium alginate has different melting points due to its different molecular weights. The larger the molecular weight, the higher the melting point. Under the premise of using sodium alginate with a high molecular weight as much as possible, sodium alginate with the above melting point can be fully melted during the reaction.
[0012] Preferably, the particle size of nano silicon nitride is 30nm-80nm.
[0013] Preferably, 1 / 3-1 / 2 weight portion of the nano silicon nitride is connected to the surface with KH560 silane coupling agent.
[0014] In specific implementation, the epoxy group in the KH560 silane coupling agent can react with the end group of PA6, thereby increasing the viscosity of the PA6 phase, reducing the melt viscosity ratio of PPO / PA6, and further promoting the compatibility of PPO and PA6.
[0015] The present invention also discloses a method for preparing a battery packaging material used for power battery packaging, comprising the following steps:
[0016] Step 1, mixing nano silicon nitride and maleic anhydride in an organic solvent, reacting under heating, constant temperature stirring, oxygen-free and water-removing environment, and then separating the fixed substance and drying it to obtain a first product;
[0017] Step 2, mixing the first product and sodium alginate, heating and stirring at a constant temperature, adding a catalyst to react in an oxygen-free environment, and drying to obtain a second product;
[0018] Step three, after the second product, polyphenylene ether and nylon 6 are mixed, the battery packaging material used for power battery packaging is obtained.
[0019] In the specific implementation, since it is relatively easy for maleic anhydride and nano silicon nitride to undergo a monoesterification reaction in step 1, but strict water removal is required, an oxygen-free water removal environment is used to obtain the first product; the first product is grafted with maleic anhydride through a monoesterification reaction, and a carboxyl group is formed by the reaction; when the first product and sodium alginate are mixed and reacted in water, the hydroxyl group on the sodium alginate and the carboxyl group on the first product undergo a double esterification reaction, and the sodium alginate is grafted on the nano silicon nitride to form a second product; finally, the second product, polyphenylene ether and nylon 6 are kneaded by a banburying method to obtain a battery packaging material, and at this time, the sodium alginate can be generated with nylon 6 Hydrogen bonds are formed with the -OH end groups and -O- segments of polyphenylene ether to make the second product more stable, increase the difficulty of decarboxylation of the sodium alginate part in the second product due to excessively high temperature during the banburying of the second product, reduce the occurrence of decarboxylation, and thus ensure the stability of the second product during banburying. At the same time, nano silicon nitride reacts with the -OH end groups of polyphenylene ether, and nano silicon nitride as inorganic rigid particles and chemical crosslinking points can reduce the melt viscosity ratio of PPO / PA6 and promote the compatibility of PPO and PA6, thereby further improving the processing performance and mechanical properties of PPO.
[0020] Preferably, in step 1, the organic solvent is acetone, the heating temperature is 60°C-70°C, the stirring rate is 1500-2000rpm, and the reaction time is 1.5-2h;
[0021] In the step 2, the heating temperature is 100°C-120°C, the stirring rate is 1000-2000rpm, and the reaction time is 1-1.5h;
[0022] In the step 3, the banburying temperature is 240° C.-270° C., the banburying stirring rate is 70-80 r / min, and the reaction time is 10-15 min.
[0023] In a specific implementation, maleic anhydride can be melted at 60°C-70°C to promote the reaction of maleic anhydride, and sodium alginate can be melted at 100°C-120°C to promote the reaction of sodium alginate.
[0024] Preferably, the nano silicon nitride in step 1 is heated to 160° C.-180° C. and dried for 1-2 hours before the reaction.
[0025] In specific implementation, this heating step can make the ——OH and ——NH 2 The number of reaches a larger value, thereby making the grafting sites on the surface of nano-silicon nitride reach a better value.
[0026] Preferably, the catalyst used in step 2 is potassium persulfate or ammonium persulfate, which is added after the system temperature in step 2 reaches 100°C-120°C.
[0027] Preferably, the weight ratio of the first product to sodium alginate is 12-15 parts:4-5 parts.
[0028] Preferably, 4A molecular sieve is used as the desiccant in the reaction process of step 2.
[0029] In specific implementation, the use of this type of molecular sieve can avoid the introduction of calcium ions, thereby facilitating the gelation of sodium alginate to prevent subsequent reactions from being hindered.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention introduces nano silicon nitride with high thermal stability and good mechanical properties, which can avoid or reduce the damage of battery packaging materials under high thermal shock and high mechanical shock, and creatively grafts maleic anhydride onto the -OH group of nano silicon nitride to make it undergo a monoesterification reaction, and then reacts the -OH group on sodium alginate with the -COOH group on maleic anhydride monoester through a double esterification reaction, thereby grafting sodium alginate onto the nano silicon nitride. Sodium alginate can generate hydrogen bonds with nylon 6, and generate hydrogen bonds with the -OH end group and -O- segment of polyphenylene ether. The formation of hydrogen bonds can make the second product more stable, increase the difficulty of decarboxylation of the sodium alginate part in the second product due to the high temperature during the banburying of the second product, reduce the occurrence of decarboxylation, and thus ensure the stability of the second product during banburying. At the same time, it reacts with the -OH end group of polyphenylene ether, and nano-silicon nitride as an inorganic rigid particle and chemical cross-linking point can reduce the melt viscosity ratio of PPO / PA6 and promote the compatibility of PPO and PA6, thereby further improving the processing performance and mechanical properties of PPO. DETAILED DESCRIPTION
[0032] The battery packaging material used for power battery packaging of the present invention is mainly prepared from the following components: 4-5 parts of sodium alginate, 8-10 parts of nano silicon nitride, 4-5 parts of maleic anhydride, 100-120 parts of polyphenylene ether, and 10-12 parts of nylon 6.
[0033] The preparation method adopted is summarized as follows:
[0034] The method comprises the following steps: step 1, mixing nano silicon nitride and maleic anhydride in an organic solvent, reacting at a constant temperature of 60-70°C, in an oxygen-free dehydration environment and at 1500-2000rpm with stirring, reacting for 1.5-2h, separating the fixed substance and drying to obtain a first product; mixing the first product with sodium alginate and stirring at a constant temperature, reacting at a constant temperature of 100-120°C, in an oxygen-free environment, with a catalyst and at 1000-2000rpm with stirring, reacting for 1-1.5h, and drying to obtain a second product; step 3, mixing the second product, polyphenylene ether and nylon 6 by a banburying method at a temperature of 240-270°C and a rotation speed of 70-80r / min for 10-15min to obtain a battery packaging material.
[0035] The battery packaging material used for power battery packaging described in the present invention has the advantages that nano silicon nitride with high thermal stability and good mechanical properties is introduced, and the damage of the battery packaging material can be avoided or reduced under high thermal shock and high mechanical shock. Maleic anhydride is creatively grafted onto the -OH group of nano silicon nitride to cause a monoesterification reaction, and then the -OH group on sodium alginate reacts with the -COOH group on maleic anhydride monoester through a double esterification reaction, thereby grafting sodium alginate onto the nano silicon nitride. Sodium alginate can form hydrogen bonds with nylon 6 and with the - The -OH end group and the -O- segment form hydrogen bonds. The formation of hydrogen bonds can make the second product more stable, increase the difficulty of decarboxylation of the sodium alginate part in the second product due to high temperature during the banburying of the second product, reduce the occurrence of decarboxylation, and thus ensure the stability of the second product during banburying. At the same time, it reacts with the -OH end group of polyphenylene ether. Nano-silicon nitride, as an inorganic rigid particle and chemical cross-linking point, can reduce the melt viscosity ratio of PPO / PA6 and promote the compatibility of PPO and PA6, thereby further improving the processing performance and mechanical properties of PPO.
[0036] The technical solution of the present invention is described in detail below through examples and comparative examples. Unless otherwise specified, the products used can be obtained from the market.
[0037] Example 1
[0038] A battery packaging material used for power battery packaging uses 4 parts of sodium alginate, 8 parts of silicon nitride with a particle size of 50 nanometers, 4 parts of maleic anhydride, 120 parts of polyphenylene ether, and 12 parts of nylon 6.
[0039] The preparation method adopted is summarized as follows:
[0040] The method comprises the following steps: step 1, mixing nano silicon nitride and maleic anhydride in acetone, reacting at a constant temperature of 60°C, an oxygen-free dehydration environment and 1500 rpm, filtering out solid matter after reacting for 1.5 hours and drying in the oxygen-free dehydration environment to obtain a first product; mixing the first product with sodium alginate and stirring at a constant temperature, reacting at a constant temperature of 100°C, an oxygen-free environment, potassium persulfate and 1000 rpm, and drying after reacting for 1 hour to obtain a second product; step 3, kneading the second product, polyphenylene ether and nylon 6 at 270°C and a rotation speed of 80 r / min for 15 minutes by a banburying method to obtain a battery packaging material.
[0041] Example 2
[0042] A battery packaging material used for power battery packaging comprises 5 parts of sodium alginate, 10 parts of silicon nitride with a particle size of 80 nanometers, 5 parts of maleic anhydride, 100 parts of polyphenylene ether, and 10 parts of nylon 6.
[0043] The preparation method adopted is summarized as follows:
[0044] The method comprises the following steps: step 1, mixing nano silicon nitride and maleic anhydride in acetone, reacting at a constant temperature of 70°C, an oxygen-free dehydration environment and 2000 rpm, filtering out solid matter after reacting for 2 hours and drying in the oxygen-free dehydration environment to obtain a first product; mixing the first product with sodium alginate and stirring at a constant temperature, reacting at a constant temperature of 120°C, an oxygen-free environment, ammonium persulfate and 2000 rpm, reacting for 1.5 hours and drying to obtain a second product; step 3, kneading the second product, polyphenylene ether and nylon 6 at 240°C and a rotation speed of 70 r / min for 10 minutes by a banburying method to obtain a battery packaging material.
[0045] Example 3
[0046] A battery packaging material used for power battery packaging, this embodiment is different from the first embodiment in that silicon nitride with a particle size of 30 nanometers is used. The rest is the same as the first embodiment.
[0047] Example 4
[0048] A battery packaging material used for power battery packaging. The difference between this embodiment and embodiment 1 is that the nano silicon nitride is dried at 160° C. for 1.5 hours before the reaction, and the rest is the same as embodiment 1.
[0049] Example 5
[0050] A battery packaging material used for power battery packaging. The difference between this embodiment and embodiment 1 is that 1 / 3 of the nano silicon nitride carries KH560.
[0051] Comparative Example 1
[0052] A battery packaging material, this comparative example is different from Example 1 in that sodium alginate is not added, and the rest is the same as Example 1
[0053] Comparative Example 2
[0054] A battery packaging material. The difference between this comparative example and Example 1 is that nano silicon dioxide with the same particle size is used instead, and the rest is the same as Example 1.
[0055] Comparative Example 3
[0056] A battery packaging material. This comparative example is different from Example 1 in that maleic anhydride is not used, and the rest is the same as Example 1.
[0057] Experimental test:
[0058] Test Standards
[0059] The tensile properties are tested according to ASTM D638 standard, and the tensile specimen size is 75×4×1mm 3 , the tensile rate is 50mm / min, the bending performance is in accordance with ASTM D790 standard, and the bending specimen size is 63.5×12.7×3mm 3 The indentation rate is 1.7 mm / min, the notched impact strength is in accordance with ASTM D256, and the impact specimen size is 63.5 × 12.7 × 3 mm 3 , V-notch, impact rate 3.5ms -1 , the pendulum weight is 0.818kg.
[0060] The results are shown in Table 1
[0061] Table 1
[0062]
[0063]
[0064] As can be seen from Table 1, the performance data of Examples 1 to 5 are better than those of Comparative Examples 1 to 3. It can be seen that the technical solution of the present invention achieves the purpose of improving the mechanical properties of battery packaging materials. The performance data of Example 1 is better than that of Comparative Example 1, indicating that in the absence of sodium alginate, sodium alginate will not generate hydrogen bonds with nylon 6, nor will it generate hydrogen bonds with the -OH end groups and -O- segments of polyphenylene ether, and thus cannot serve as an intermediary between the two to improve the compatibility of the two; even if there is a -COOH group generated by the reaction of maleic anhydride, its improvement in the compatibility of nylon 6 and polyphenylene ether is limited. The performance data of Example 1 is better than that of Comparative Example 2, indicating that when nano-silicon dioxide of the same particle size is used instead of nano-silicon nitride, the mechanical properties of nano-silicon dioxide are reduced because its own mechanical strength is lower than that of nano-silicon nitride. The performance data of Example 1 is better than that of Comparative Example 3, indicating that in the absence of maleic anhydride, sodium alginate can only react with the -OH group of nano-silicon nitride through the -COONa group, which reduces the chance of hydrogen bonding and even reaction between the -COONa group and the -OH end group of polyphenylene ether, thereby reducing the compatibility of nylon 6 and polyphenylene ether.
[0065] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, horizontal" and "top, bottom" are usually for the convenience of describing the present invention and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the scope of protection of the present invention.
[0066] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. A battery packaging material used for power battery packaging, characterized in that: The invention comprises the following components in parts by weight: 4-5 parts of sodium alginate, 8-10 parts of nano silicon nitride, 4-5 parts of maleic anhydride, 100-120 parts of polyphenylene ether and 10-12 parts of nylon 6.
2. The battery packaging material for power battery packaging according to claim 1, characterized in that: The melting point of sodium alginate is below 100°C.
3. The battery packaging material for power battery packaging according to claim 1, characterized in that: The particle size of the nano silicon nitride is 30nm-80nm.
4. The battery packaging material for power battery packaging according to claim 1, characterized in that: 1 / 3-1 / 2 weight portion of the nano silicon nitride is connected to the surface with KH560 silane coupling agent.
5. A method for preparing a battery packaging material for power battery packaging according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, mixing nano silicon nitride and maleic anhydride in an organic solvent, reacting under heating, constant temperature stirring, oxygen-free and water-removing environment, and then separating the fixed substance and drying it to obtain a first product; Step 2, mixing the first product and sodium alginate, heating and stirring at a constant temperature, adding a catalyst to react in an oxygen-free environment, and drying to obtain a second product; Step three, after the second product, polyphenylene ether and nylon 6 are mixed, the battery packaging material used for power battery packaging is obtained.
6. The method for preparing a battery packaging material for power battery packaging according to claim 5, characterized in that: In the step 1, the organic solvent is acetone, the heating temperature is 60°C-70°C, the stirring rate is 1500-2000rpm, and the reaction time is 1.5-2h; In the step 2, the heating temperature is 100°C-120°C, the stirring rate is 1000-2000rpm, and the reaction time is 1-1.5h; In the step 3, the banburying temperature is 240° C.-270° C., and the banburying stirring speed is 70-80 r / min.
7. The method for preparing a battery packaging material for power battery packaging according to claim 5, characterized in that: In the step 1, the nano silicon nitride is heated to 160° C.-180° C. before mixing and dried for 1-2 hours.
8. The method for preparing a battery packaging material for power battery packaging according to claim 5, characterized in that: In the step 2, the catalyst is potassium persulfate or ammonium persulfate, and the catalyst is added after the reaction system reaches 100° C.-120° C.
9. The method for preparing a battery packaging material for power battery packaging according to claim 5, characterized in that: In the step 2, the mass ratio of the first product to sodium alginate is (12-15):(4-5).
10. The method for preparing a battery packaging material for power battery packaging according to claim 5, characterized in that: In the step 3, the reaction time is 10-15 min.
Citation Information
Patent Citations
High-abrasion-resistance silicon nitride / nylon6 composite nano-material and preparation method thereof
CN103772973A
Graphene-functionalized polyphenyl ether / nylon 6 composite material and preparation method
CN106995604A
Nylon 6 / polyphenyl ether composition and preparation method thereof
CN107118546A
High-heat-conductivity polyphenyl ether based copper-clad plate and preparation method thereof
CN107641310A
Electric-conducting polyamide 6 / polyphenyl ether composition and preparation method thereof
CN110684347A